JPE Turnaround Times (Journal of Political Economy, 2019)
Previous article FreeJPE Turnaround TimesPDFPDF PLUSFull Text Add to favoritesDownload CitationTrack CitationsPermissionsReprints Share onFacebookTwitterLinked InRedditEmailQR Code SectionsMoreJPE Turnaround Times, Previous Two Years Outcome of 1st Round DecisionsMean Days to DecisionMedian Days to DecisionDecision Later than Six Months after Submission (as percentage of decisions within decision type)Desk Rejection55%1070%Reject with Reviews36%13610122%Revise9%21418149% Previous article DetailsFiguresReferencesCited by Journal of Political Economy Volume 127, Number 1February 2019 Article DOIhttps://doi.org/10.1086/702725 © 2019 by The University of Chicago. All rights reserved.PDF download Crossref reports no articles citing this article.